ANALYSIS THE DEVELOPMENT OF TAKALLAM PROGRAM MANAGEMENT AT AL-AZHAR PARE KEDIRI COURSE INSTITUTE - Satyaningrum, Retnowati; Bahrun, Muhammad Farhan; Al-latifatuzzahra, Siti Safira; Marlina, Leny; Hilmi, Danial (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Takallam program of Al-Azhar Pare Kediri is one of the most popular programs. This program has 3 levels in the learning process which each level has a target achievement that has been arranged systematically. The purpose of this study is to analyze the history of the development of the Takallam program of Al-Azhar Pare Kediri Course Institute from the beginning of the emergence of the program until this current time. This research uses descriptive qualitative research methods and data collection techniques through interviews and documentation. The analysis technique used through 3 stages, namely data reduction, data exposure, and conclusions. The data sources in this study are primary and secondary data sources. Primary data sources are mudir (director) and teachers of Al-Azhar Pare Kediri Course Institute, while secondary sources are books, journal houses, articles and proceedings to support the necessary theory and analysis. The results of the analysis found are that there are two phases in the development of the Takallam class at Al-Azhar Pare Kediri course institution, namely the initial phase and the development phase. The initial phase began in 2013 and the development phase began in 2022. Then three things that become the challenges of Al-Azhar Pare Kediri course institution are first, the awareness of Arabic-speaking participants or members in Al-Azhar Pare Arabic village varies, such as teachers who allow participants to speak Indonesian or speak directly to participants. Second, updating modules or materials which of course takes a long time. Third, arousing and increasing participants' interest in speaking Arabic.